The Effectiveness of Systemic Couple Therapy and Cognitive-Behavioral Couple Therapy on Sexual Intimacy and Sexual Function in Distressed Couples - Haghighat Bayan, Nazanin; Ghorbani Gherkhloo, Maryam; Sadeghi, Elahe; Soltani, Mehdi; Reyhani, Reza; Pourmohammad Ghouchani, Kamran; Nakhaei Moghadam, Roksana (KMAN Counseling & Psychology Nexus, 2025)
Distress in marital relationships can lead to diminished intimacy and the emergence of problems in sexual functioning, which over time may adversely affect psychological well-being and marital quality of life. The present study aimed to investigate the effectiveness of systemic couple therapy and cognitive-behavioral couple therapy on sexual intimacy and sexual function in distressed couples. This research employed a quasi-experimental method using a pre-test–post-test control group design. The statistical population consisted of distressed couples referred to counseling centers in Tehran, from which 30 couples were selected using convenience sampling and randomly assigned to two experimental groups and one control group. The experimental groups received ten 90-minute sessions of systemic couple therapy and cognitive-behavioral couple therapy interventions, respectively, while the control group did not receive any intervention. The findings indicated that both types of interventions led to increased sexual intimacy and improved sexual function among the couples. However, cognitive-behavioral couple therapy had a greater impact on enhancing these components. The results suggest that addressing maladaptive beliefs and behavioral patterns in cognitive-behavioral couple therapy may play a more effective role in improving the quality of sexual relationships. Accordingly, it is recommended that this approach be incorporated into intervention programs for distressed couples.